Eddy current tomography for visualization of cracks in aircraft riveted joints - Alexey Vertiy; Valentyn Uchanin; Vladimir Pavlikov; Simeon Zhyla; Olexandr Shmatko; Eduard Tserne (Радіоелектронні і комп'ютерні системи, 2021)
The control of the subsurface areas of metal products is necessary in many technological processes. So, for example, in aerospace technology it is essential to determine the presence of defects in aircraft engines. The same problems arise in chemical, power and other industries, which are letting out the highly technological equipment one of the widely known methods for inspecting metal products in the aviation industry is the eddy current method. This method is widely used to control small microscopic defects inside conductive materials. This method allows to ensure the safety of the operation of various products and devices in many areas of modern industry. An eddy current detector (probe) is a device, which induces eddy currents into metal objects and then detects the magnetic fields produced by these eddy currents. A magnetic field is created by a coil, or set of coils, through which a time-varying electrical current is driven. The frequency regime is sufficiently low, a few hertz to a few hundred kilohertz, so the targets of interest are within the near field of the transmitter. Considering the high conductivity of study samples, we can define that used waves in metals are located in the millimeter wave band. An eddy current imaging can be considered near-field imaging and a device allowing obtaining the eddy current images as a scanning near-field microscope. The obtained experimental results showed that the proposed tomographic method is effective for studying various complex inhomogeneities under the metal surface